Seroprevalence of Blood Borne Transmissible Diseases in Trauma Orthopaedic Surgical Patients - Sánchez, Luis P.; Flynn, John M.; Mayol, Magdiel (Puerto Rico Health Sciences Journal, 2014)
see manuscript